CSR Feels Good, But Does It Work? From Affective Brand Image to Customer Loyalty - Potu, Tania Monica; Banda, Hope Wilfred; Siahaya, Janice Carysa (University of Muhammadiyah Malang, 2026)
This study examines how Corporate Social Responsibility (CSR) influences customer satisfaction and customer loyalty through the mediating role of emotional brand image, addressing a short- and long-term perspectives in the fast-food industry. A hundred respondents from Jakarta who are familiar with CSR activities participated in a quantitative survey, and SPSS was used to analyze the results. The results show that CSR significantly improves emotional brand image (β = 0.668; sig = 0.000; Adj R² = 0.440), explaining 44% of the variation in brand image. However, consumer satisfaction is not substantially impacted by affective brand image (β = 0.127; sig = 0.111), indicating that short-term contentment cannot be driven only by emotional views. Conversely, consumer loyalty is strongly influenced by customer satisfaction (β = 0.477; sig = 0.000; Adj R² = 0.594), highlighting its importance for long-term outcomes. The study concludes that while CSR effectively builds emotional brand perceptions, companies must align these with actual service and product quality to achieve sustainable satisfaction and loyalty.